ANALISIS EFEKTIFITAS KOMUNIKASI ANTARA CONTROLLER DAN PENERBANG DI UNIT APPROACH JAKARTA SEKTOR TERMINAL WEST JAKARTA AIR TRAFFIC SERVICES CENTRE - Iwan Ardiansyah (Operations Excellence: Journal of Applied Industrial Engineering, 2015)
Abstract. This study aims to recognize the effectivity level of controller-pilotcommunication at Terminal West Sector in Jakarta Approach, Jakarta Air TrafficServices Centre, to know the influence of communication factors toward theeffectivity and the solusion to keep the effectivity level of communication basedon PDCA concept. The first analysis methode is right side analysis which statesthat each of the usage of standard phraseology and the performance ofcommunication facilities is less than the standard value. The second is singlecorrelation analysis which states that message structure has a strong and positivecorrelation to the effectivity as 0,61, the condition of communication facilities hasa medium and positive correlation to the effectivity as 0,48, and the number ofaircraft movement has a weak and positive correlation to effectivity as 0,29. Thethird is multiple correlation methode with three independent variables whichstates that the message structure, the condition of communication facilities and thenumber of aircraft movement togetherly have a positive correlation to effectivity.Factors must be fixed are the training programme for controllers and supervisor'sreporting culture by conducting procedures such as pre-work briefing, post-workevaluation, the completeness of reporting and regular refreshing training.Keywords: Effectivity, aeronautical communication, right side analysis,correlation analysis, PDCA